2018
DOI: 10.1145/3231712
|View full text |Cite
|
Sign up to set email alerts
|

Errors and Complications in SQL Query Formulation

Abstract: SQL is taught in almost all university level database courses, yet SQL has received relatively little attention in educational research. In this study, we present a database management system independent categorization of SQL query errors that students make in an introductory database course. We base the categorization on previous literature, present a class of logical errors that has not been studied in detail, and review and complement these findings by analyzing over 33,000 SQL queries submitted by students… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
75
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(94 citation statements)
references
References 32 publications
8
75
0
Order By: Relevance
“…SQL as a language and the formulation of SQL queries can be complex for novices. Several studies have reported about the types of mistakes and errors students encounter when learning to write SQL [3,4,9,37,41,42]. Performance in writing SQL is also linked with students' course performance [2].…”
Section: Learning and Teaching Sqlmentioning
confidence: 99%
“…SQL as a language and the formulation of SQL queries can be complex for novices. Several studies have reported about the types of mistakes and errors students encounter when learning to write SQL [3,4,9,37,41,42]. Performance in writing SQL is also linked with students' course performance [2].…”
Section: Learning and Teaching Sqlmentioning
confidence: 99%
“…Alternatively, the environment may be a DBMS's SQL interface embedded in a web page, and the web page fitted with auxiliary elements, for example, a representation of the underlying database schema, a natural language request (i.e., data demand) to which a students must write an SQL equivalent, and the correct result table [101]. The database may be represented at the conceptual level as an Entity-Relationship (ER) diagram [37], or at the logical level as a database schema diagram [43].…”
Section: Learning Contextmentioning
confidence: 99%
“…Furthermore, semantic errors have been further divided into errors which are evident without knowledge of the underlying data demand, and errors which are only recognizable if the data demand is known [17]. The former kind of semantic errors are called semantic, and the latter logical [101].…”
Section: Learning Contextmentioning
confidence: 99%
See 2 more Smart Citations